The benefits of social capital and social entrepreneurship: https://doi.org/10.5937/etp2501095M - Mitrović, Vladimir; Dević, Željko; Terzić, Ivana (Ekonomija - teorija i praksa, 2025)
The subject of this paper is the impact of social capital on entrepreneurial activity. The aim of the research is to theoretically and empirically examine the relationship between social capital and entrepreneurial activity, as well as to explore current social processes within the social entrepreneurship entities in the southern and Eastern regions of Serbia. The first part of the paper analyzes social capital as the presence of trust, norms, and social networks, which facilitate organized action for the benefit of individuals and society as a whole. The second part focuses on the benefits of social capital relevant to entrepreneurs. The third section presents the results of the research and a discussion of these results, concluding that the potential of social capital has not been sufficiently recognized by social entrepreneurship entities in southern and Eastern Serbia. Finally, the paper concludes that the success of entrepreneurial activity largely depends on numerous social factors, making it essential to examine all specific elements that may influence entrepreneurship development. Accordingly, the study of the significance of social capital has proven indispensable. Relevant literature was used throughout the paper, and in this context, scientific and theoretical insights, as well as contemporary business practices, were examined using methods such as induction, deduction, analysis, synthesis, abstraction, generalization, observation, and content analysis.